Cover Feature: Dynamic Protein–Metal Ion Networks: A Unique Approach to Injectable and Self‐Healable Metal Sulfide/Protein Hybrid Hydrogels with High Photothermal Efficiency (Chem. Eur. J. 25/2018). Issue 25 (24th March 2018) - Wang, Liqiang; Liang, Kaixin; Jiang, Xingxing; Yang, Minghui; Liu, You‐Nian
Abstract : Dynamic protein–metal ion networks were developed for the fabrication of adaptable hydrogels with both injectable and self‐healable features. Metal ions can react with cysteine residues of the protein to in situ transform into metal sulfide NPs, leading to the formation of injectable, self‐healable and metal sulfide embedded hybrid hydrogels with high photothermal efficiency, which can be utilized for photothermal therapy against tumors. More information can be found in the Full Paper by M. Yang, Y.‐N. Liu, et al. onpage 6557 .